1970
DOI: 10.1111/j.1469-1809.1970.tb00215.x
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the difference in measured intelligence between twins and single births*

Abstract: SUMMARYMean V.R. (verbal reasoning) scores recorded in the eleven‐plus examination for Birmingham multiple births in the years 1950‐57 were 95‐7 for 2164 twins and 91‐6 for 33 triplets. The mean for 48,913 single children born in the years 1950‐54 was 100‐1.The low scores of twins are not explained by differences from single births in their distributions by maternal age and birth order or by birth weight and duration of gestation. They are also not accounted for by the increased risks associated with monozygos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
79
1
1

Year Published

1978
1978
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(88 citation statements)
references
References 12 publications
7
79
1
1
Order By: Relevance
“…In the Collaborative Perinatal Project of the United States, twins raised as singletons scored at the same level as twins, suggesting a prenatal origin to their lower mental scores (Myrianthopoulos et al, 1976). On the other hand, the Birmingham, United Kingdom, study found that in cases where one twin was stillborn or died in the first 4 weeks of life, surviving twins scored almost at singleton levels (Record et al, 1970). They concluded that 'the large differences in weight and duration of gestation between single and multiple births do not result in appreciable score differences ' (p. 19).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the Collaborative Perinatal Project of the United States, twins raised as singletons scored at the same level as twins, suggesting a prenatal origin to their lower mental scores (Myrianthopoulos et al, 1976). On the other hand, the Birmingham, United Kingdom, study found that in cases where one twin was stillborn or died in the first 4 weeks of life, surviving twins scored almost at singleton levels (Record et al, 1970). They concluded that 'the large differences in weight and duration of gestation between single and multiple births do not result in appreciable score differences ' (p. 19).…”
Section: Discussionmentioning
confidence: 96%
“…It would be interesting to quantify twin-twin differences in the quality of intrauterine environment and correlate this with mental ability discordances between twin pairs. One possible indicator might be birthweight, which was found to be associated with twin score decrements in some twin studies (Alin Akerman & Fischbein, 1991;Record et al, 1970). Twins have a smaller birthweight, and birthweight is related to intelligence test scores in childhood .…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of large twin and sibling studies give consistent results (e.g. Record et al, 1970), the weight now resides with adoption studies with greater attention paid to the estimation of placement effects which lead to overestimation of the familial environment.…”
Section: Discussionmentioning
confidence: 99%
“…The estimates of the difference in intelligence range from 5.1 to only 0.5 IQ points in studies from different countries, populations, and birth cohorts. Several studies based on birth cohorts from many years ago found a lower intelligence in twins (Record et al, 1970;Deary, Pattie, Wilson, & Whalley, 2002;Ronalds, de Stavola, & Leon, 2005). However, prenatal and perinatal care has improved in the past decades, which may have reduced this difference in cognitive ability between twins and singletons.…”
mentioning
confidence: 99%
“…The question of whether twins differ from singletons in their cognitive abilities due to the risk factors associated with their twin status has been the focus of research for a long time (Hay & O'Brien, 1983;Record, McKeown, & Edwards 1970;Vandenberg, 1984). A recent meta-analysis of studies on differences in intelligence between twins and singletons concluded that, on average, twins seem to have lower IQs than singletons (Voracek & Haubner, 2008).…”
mentioning
confidence: 99%